Macroinvertebrate community composition and richness along extreme gradients: The role of local, catchment, and climatic variables in Patagonian headwater streams. (4th December 2021) - Astorga Roine, Anna; Reid, Brian; Uribe, Luis; Moreno‐Meynard, Paulo; Fierro, Pablo; Madriz, Isaí; Death, Russell G.
Abstract: We investigated how interacting multi‐scale environmental variables affect taxonomic composition and functional feeding groups of macroinvertebrates in headwater streams of western Patagonia in southern Chile (45–47°S), a region characterised by extreme climatic gradients, intact forested catchments, and recent intense land use change. The opportunity of establishing biological/functional diversity patterns for near‐reference conditions of headwaters streams is paramount. We used multi‐dimensional scaling ordination and boosted regression tree analysis to evaluate the link between reach, catchment, spatial, and regional climatic variables and macroinvertebrate community structure. The high diversity of predators in low productivity streams, together with genera previously unreported for this latitudinal range underscore the unique characteristics and very limited understanding of Patagonian freshwater stream communities. Two main groups of environmental variables were linked to both taxonomic and functional feeding group diversity. The strongly associated variables were related to forest cover (and inversely alpine zone) at the catchment scale, together with stream velocity at the local scale. The second group reflected local indicators of productivity and weathering inputs, associated with the regional east–west precipitation gradient. We present a conceptual model for the catchment scale effects on invertebrate functional groups in forested headwater streams. While the results highlight potentially singular characteristics of the study region, they also suggest a macro‐ecological generalisation of how global change variables, operating on mountain catchments, may differentially affect stream ecosystems as a consequence of the variations in the forest/alpine gradient, across both deciduous and evergreen temperate biomes.